Bibliometria e análise de conteúdo sobre o ensino por competências na educação em engenharia de materiais - Lopes, Mariana Salgado (Universidade Federal de São Carlos, 2022)
Engineering education is a field of great importance, due to its ability to graduate strategic professionals to support the socioeconomic growth of the countries. Materials Engineering, for instance, emerged in Brazil with the objective of improve a better use of materials and adding technological concepts that help the generation of wealth for the country. However, for these professionals to be able to perform their role properly, there is a need for holistic education, providing a solid technical base and the soft skills necessary to perform professionally. Thus, much has been debated in recent years about the need to update engineering education around the world. The goal of this work is to aid the teaching and implementation of soft skills in the Materials Engineering course program in the Federal University of São Carlos, through an analysis of bibliometric indicators in competency-based learning publications indexed in the Web of Science database from 2001 to 2020, and content analysis of the new National Curricular Guidelines, the pedagogical course project and the Institutional Modernization Project. The indicators showed a significant increase in the number of publications over the years, indicating a growing interest in this topic. The USA leads in the number of publications in the area, concentrating institutions and researchers with the highest number of publications. A significant portion of the analyzed publications resulted from events on Engineering Education, highlighting the importance of their realization and indexing of publications in databases. The content analysis indicates the need for a greater alignment between the objective of building competences and the pedagogical activities provided for in the course. It was possible to conclude that, the use of unconventional analytical methodologies in the field of Engineering Education, represents a big potential in the investigation of new improving sources in the modernizations of the graduation courses.
Bibliometrics and content analysis on competence-based learning in materials engineering education
Keywords: Educação em engenharia; Ciência e engenharia de materiais; Ensino por competências; Bibliometria; Análise de conteúdo; Engineering education; Materials science and engineering; Competence-based learning; Bibliometrics; Content analysis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA EXTRATIVA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA